KEPEMIMPINAN, BUDAYA DAN KINERJA ORGANISASI SEBUAH KEYWORD KEBERHASILAN - Mursid, Ali (PRESTASI, 2009)
Leadership is the most important role to increase organiÂzational performance. This article tells about the role of leadership in creating the organizational culture, however when the organization built based on the value that the founder formulated and the leader is a part of the object that must follow it. Strong leadership is able to change the culture that influence the behavior and custom of organization and it will influence the organization performance to have superior and competitive advantage.Keyword : Leadership, Culture, Organizational Performance